Does moving to the music make you smarter? The relation of sensorimotor entrainment to cognitive, linguistic, musical, and social skills. (September 2019) - Maróti, Emese; Barabás, Edina; Deszpot, Gabriella; Farnadi, Tamara; Norbert Nemes, László; Szirányi, Borbála; Honbolygó, Ferenc
Several studies have shown the benefits of music training on multiple musical and non-musical skills. Because our perception of music is inherently rhythmic, it is possible that the underlying mechanism of the transfer effect of music is rhythmic entrainment. Previous studies found transfer effects of sensorimotor entrainment (SE), a form of rhythmic entrainment, but, to date, there has been no comprehensive study that has examined long-term effects of SE in multiple domains. In this study, we compared the transfer effects of two different SE-based (one with fixed rules, the other with free movement) music education methods and a singing-based (control) method on cognitive, linguistic, musical, and social skills in 6–7-year-old children. On the initial assessment, there were no significant differences in performance between the three groups. After 8 months, we found significant improvement for the entrainment-based methods compared to the singing-based method in pitch discrimination, working memory, phonological processing, and verbal skills, and the singing-based method improved executive functions more compared to the SE-based methods. Additionally, we found significant correlations between SE and attention, working memory, and phoneme awareness. Finally, we showed that different teaching methods of SE (rule-based vs. free movement) resulted in different transfer effects.